Seed systems in Tanzania - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Seed systems, higher productivity and commercialization: Prospects for sorghum and millets in Tanzania, SADC/ICRISAT Sorghum and Millet Improvement Program, Bulawayo, Zimbabwe. 1999. 96 pp.